Kinematic Analysis of a Dynamic Balance Task by Children Who Are Deaf. - Sabbatical Report - Martens, David (Spring;Exercise Science., 1998)
Keywords: dept.hms; faculty_collection; sabbatical_report

Kinematic analysis of a dynamic balance task by children who are deaf - Butterfield, S.A.; Lehnhard, R.A.; Martens, D.; Moirs, K. (Clinical Kinesiology, 1998)
The purpose of this investigation was to identify dynamic balance strategies used by 18 boys and girls who were deaf. Each child was simultaneously videotaped from the frontal and sagittal planes while walking forward on a balance beam and stepping over a stick placed knee high. Next their performance was evaluated on a pass-fail basis. Following testing, each participant was assigned to the respective group (pass n = 9; fail n = 9) for kinematic analysis. Based on a discriminant function analysis of the data, head and trunk ranges of motion (ROM) were significant (p < .05) predictors of pass/fail performance. Children in the fail group had significantly greater head and trunk sway causing them to lose balance. Factors contributing to poor dynamic balance among children who are deaf are discussed as are implications for intervention and further research.
Keywords: Deaf; Dynamic balance; Proprioception; Vestibular; adolescent; article; child; clinical article; dept.hms; discriminant analysis; female; head movement; hearing impairment; human; male; proprioception; trunk; videotape; ⛔ No DOI found

Counseling Skills and the Athletic Therapist - Misasi, S.P.; Kemler, D.S.; Redmond, C.J. (Athletic Therapy Today, 1998)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms